2018
DOI: 10.1042/bsr20180849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FM0807, a novel curcumin derivative, on lipopolysaccharide-induced inflammatory factor release via the ROS/JNK/p53 pathway in RAW264.7 cells

Abstract: Purpose: Sepsis is a systemic inflammatory response caused by infection. Curcumin is known to have antioxidant and anti-inflammatory activities. FM0807, a curcumin derivative, was investigated in the present study to determine its effect on cytokines and the possible molecular mechanism. Main methods: The experiments were carried out in lipopolysaccharide (LPS)-induced RAW 264.7 cells. Cell viability was measured by MTT assay. ELISA, Griess assays, fluorescence-based quantitative PCR, flow cytometric analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Curcumin can improve the condition in sepsis due to its anti-inflammatory, antioxidant and immunomodulatory properties. Curcumin inhibits the secretion of plasma TNF-α and IL-6, the activation of MAPKs, and the production of reactive oxygen species (ROS) which relate to inflammatory response [ 9 , 10 ]. Curcumin acts on MAPK p38 pathway modulating COX-2 and iNOS expression in chronic experimental colitis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin can improve the condition in sepsis due to its anti-inflammatory, antioxidant and immunomodulatory properties. Curcumin inhibits the secretion of plasma TNF-α and IL-6, the activation of MAPKs, and the production of reactive oxygen species (ROS) which relate to inflammatory response [ 9 , 10 ]. Curcumin acts on MAPK p38 pathway modulating COX-2 and iNOS expression in chronic experimental colitis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The half-life of FM0807 in various solutions of pH 2–9 was longer than 2 days. FM0807 is more stable than its precursor: curcumin [16]. It was shown that FM0807 had a substantial inhibitory effect on acute and chronic inflammation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress and inflammation are intertwined and affect each other. Studies have shown that ROS is the major inducement of inflammation [ 37 ], while TNF-α is the main cytokine that induces inflammation; the increase of TNF-α promotes the production of ROS and up-regulates the oxidative stress response [ 38 ]. IL-1β is the main active form of interleukin-1 (IL-1), an important pro-inflammatory cytokine in the body that participates in the regulation of the immune response and inflammatory reaction process [ 39 ].…”
Section: Discussionmentioning
confidence: 99%